Logistics Processes and Systems Design Using Computer Simulation - Krajcovic, Martin; Stefanik, Andrej; Dulina, Luboslav (Communications - Scientific letters of the University of Zilina, 2016)
In the course of logistics systems designing, great emphasis has been recently put on speed, quality and flexibility of the proposed solutions. The logistics system draft requires then not only an analysis of the logistics systems requirements, a draft of several solution variants and their static verification but also dynamic verification of performance of the designed system in real conditions in a form of computer simulation. The following article deals with the issues of the use of computer simulation for logistics processes and systems designing.